Quantitative characterization of all single amino acid variants of a viral capsid-based drug delivery vehicle - Emily C. Hartman (Nature Portfolio, 2018)
Self-assembling proteins have important applications in industrial technologies, but it is difficult to predict how mutations affect assembly. Here the authors present SyMAPS, coupling comprehensive codon mutagenesis with high-throughput sequencing, and apply it to bacteriophage capsid protein.